2019
DOI: 10.1002/ajp.23044
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional composition of the diet of the western gorilla (Gorilla gorilla): Interspecific variation in diet quality

Abstract: To meet nutritional needs, primates adjust their diets in response to local habitat differences, though whether these dietary modifications translate to changes in dietary nutrient intake is unknown. A previous study of two populations of the mountain gorilla (MG: Gorilla beringei) found no evidence for intraspecific variation in the nutrient composition of their diets, despite ecological and dietary differences between sites. One potential explanation is that nutritional variability in primate diets requires … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(41 citation statements)
references
References 114 publications
1
40
0
Order By: Relevance
“…Virunga mountain gorillas rely on an almost entirely folivorous diet that is both spatio-temporally abundant and high in protein, while western lowland gorillas rely most heavily on unpredictable, seasonal fruit in addition to herbs and leaves. The western lowland gorilla diet is comparatively lower in protein, but high in non-protein energy during periods of high fruit consumption [ 20 , 23 , 45 ]. When fruit-feeding, gorillas spend more time travelling and less time resting [ 45 ], which, in addition to competition with other apes and the comparative unpredictability of their ecological conditions, might provide differential sources of environmental stress.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Virunga mountain gorillas rely on an almost entirely folivorous diet that is both spatio-temporally abundant and high in protein, while western lowland gorillas rely most heavily on unpredictable, seasonal fruit in addition to herbs and leaves. The western lowland gorilla diet is comparatively lower in protein, but high in non-protein energy during periods of high fruit consumption [ 20 , 23 , 45 ]. When fruit-feeding, gorillas spend more time travelling and less time resting [ 45 ], which, in addition to competition with other apes and the comparative unpredictability of their ecological conditions, might provide differential sources of environmental stress.…”
Section: Discussionmentioning
confidence: 99%
“…Second, we assess whether gorillas that experience more environmental stress exhibit more pronounced facial FA. While environmental stress encompasses many factors, one main axis of variation among gorilla subspecies lies in dietary and ecological variability, with western lowland gorillas being exposed to the highest level of seasonal unpredictability in food resources and competition [ 20 ]. Western lowland gorillas have also experienced major population declines due to human activity and infectious diseases, most notably Ebola, resulting in approximately 90% casualties in affected populations [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…b . graueri ), and mountain gorillas in several study sites (western lowland gorillas: Mondika in Lodwick & Salmi, 2019, Bai Hokou in Goldsmith, 1999; Remis, 1997, Nouabalé‐Ndoki in Nishihara, 1995, LopĂ© in Rogers et al, 1990; Williamson et al, 1990, Rio Muni in Sabater Pi, 1997, Belinga in Tutin & Fernandez, 1985, reviewed in Rogers et al, 2004, and eastern lowland gorillas: Kahuzi‐biega in Yamagiwa et al, 1994; Yamagiwa et al, 2005, and mountain gorillas: Bwindi in Rothman et al, 2006). Furthermore, it is also reported that chimpanzees and bonobos in multiple study sites feed on piths of African gingers in the wild (chimpanzees: Belinga in Tutin & Fernandez, 1985, Bulindi in McLennan, 2013, Kahuzi‐biega in Yamagiwa & Basabose, 2006, Kalinzu in Furuichi et al, 2001, Kibale in Potts et al, 2011, LopĂ© in Tutin & Fernandez, 1993, Mahale in Nishida & Uehara, 1983, and bonobos: Bolobo in Maloueki et al, 2016, Lake Tumba in Horn, 1980, Wamba in Ishizuka et al, 2019, and Yalosidi in Kano, 1983; Uehara, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…b. graueri), and mountain gorillas in several study sites (western lowland gorillas: Mondika in Lodwick & Salmi, 2019, Bai Hokou in Goldsmith, 1999Remis, 1997, NouabalĂ©-Ndoki in Nishihara, 1995, LopĂ© in Rogers et al, 1990Williamson et al, 1990, Rio Muni in Sabater Pi, 1997, Belinga in Tutin & Fernandez, 1985 in Rogers et al, 2004, and eastern lowland gorillas: Kahuzi-biega in Yamagiwa et al, 1994;Yamagiwa et al, 2005, and mountain gorillas:…”
Section: Application Of African Ginger Feedingmentioning
confidence: 99%